Kajian Tafsir di Indonesia - rohman, Taufikur (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2012)
Indonesia is the country with the largest Muslim population in the world. It is of course also has a significant correlation with the need for a true understanding of the Koran as the main guideline in the life of a Muslim. This paper attempts to discuss the development of interpretation studies in Indonesia. However, because of the many works of commentary that exist in Indonesia, then this paper will explain in more detail in the full interpretation 30 chapters, while the commentaries that are thematic, and which only focus on certain papers will cover more briefly author so hopefully this study will cover the whole work of interpretation that exist in Indonesia comprehensively but solid content. The development of the interpretation of the Koran in Indonesia is somewhat different. Study commentary in the Arab world develop quickly and rapidly, because Arabic is the language, so they do not experience significant difficulties to understand the Koran. This is different to the Indonesian people whose native language is not Arabic.